Perilaku Semantis Preposisi ʿAlā pada Arbain an-Nawawi - Majid, Muhammad Fauzan; Imamuddin, Basuni (Universitas Al Azhar Indonesia, 2025)
This paper focuses on the semantic study of the preposition ʿalā in Arbain an-Nawawi published by Pustaka Syabab. This article analyzes the meaning, function, translation shift and equivalents of the preposition ʿalā descriptively analytically. This paper is designed qualitatively, and data collection is carried out using documentary technique. This paper uses the classification of the meaning of the preposition على /ʿalā/ according to al-Ghalayini and Leech’s concept of meaning. This study analyzes to find the preposition ʿalā that is not directly connected to a personal pronoun in each hadith, and find their semantic meaning. The results of the study show that the preposition ʿalā that are not directly connected to the personal pronoun in Arbain an-Nawawi is 23 prepositions. The preposition ʿalā meaning isti’lā` totals 5 (21.7%), mujāwazah totals 5 (21.7%), taʿlīl totals 2 (8.7%), ibtidā` al-ghāyah totals 1 (4.35%), ilṣāq totals 1 (4.35%), ẓarfiyyah totals 8 (34.8%), and istidrāk totals 1 (4.35%). ʿAlā contains 23 conceptual prepositions, 23 thematic prepositions, 7 connotative prepositions, 4 social prepositions, 8 affective prepositions, 2 reflective prepositions, and 9 collocative prepositions. This article can be a reference for Arabic-Indonesian translation of the preposition ʿalā’s meaning for contextual translation types and its equivalents.Keywords - ʿalā, Equivalent, Preposition. Semantics.